Measurement of the electron structure function F-2(e) at LEP energies - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (Elsevier, 2014)
The hadronic part of the electron structure function F2e has been measured for the first time, using e +e - data collected by the DELPHI experiment at LEP, at centre-of-mass energies of s=91.2-209.5GeV. The data analysis is simpler than that of the measurement of the photon structure function. The electron structure function F2e data are compared to predictions of phenomenological models based on the photon structure function. It is shown that the contribution of large target photon virtualities is significant. The data presented can serve as a cross-check of the photon structure function F2γ analyses and help in refining existing parameterisations. © 2014 The Authors. Elsevier B.V.